الاستراتيجيات الخطابية في القصة القرآنية - خطابات سيدنا نوح عليه السلام لقومه أنموذجا - عيشوش, نعيمة (جامعة الوادي - University of Eloued, 2021)
يهدف هذا المقال لإبراز أهمية و أهداف تنوّع استراتيجيات الخطاب القرآني لنفس الشخصية في القصص القرآني المفتوح في مقامات تلفظيّة مختلفة، ذلك أنّ الخطابات هي انجاز للأفعال الكلامية في مقام تلفظي محدّد، و دلالة الأفعال الكلامية تتعدد بحسب مقصدية المرسل (الله عزّ و جل) من خلال المواءمةبينالشكلاللّغويالمناسب،وبينالعناصر المقامية(مقام نزول الخطاب القرآني بكل ملاباساته على المتلفّظ له الأوّل الرسول محمد صلى الله عليه وسلم ، و المتلفّظ لهم من بعده سواء صحابته المؤمنين أو كفار قريش )،و تتحدّد مقصدية الخطاب إذن بواسطة تتبع كيفية توظيف الأفعال الكلامية المجسّدة للخطاب حسب المقامالذي ورد فيه بكل ملابساته بدلالتقيّدبالمعنىاللّغويفقط. This article aims to highlight the importance and objectives of the diversity of Qur’anic discoursestrategies for the samecharacter in the open Qur’anic stories in different verbal positions, because speeches are the implementation of verbal actions and the significance of verbal actions varies according to the intent of the sender (GodAlmighty) throughmatching the appropriatelinguisticform. And among the denominativeelements (the shrine of the revelation of the Qur’andiscourse on the one whowasenunciated by the Messenger Muhammad, mayGodblesshim and granthimpeace), and the intention of the speech isthusdetermined by tracking how the verbal actions embodying the discourse are employedaccording to the place in whichitisstatedwith all itscircumstancesinstead of beingrestricted to the linguisticmeaningonly.
- Discourse Strategies In The Quranic Story - The Speeches Of Noah, Peace Be Upon Him, To His People As A Model–
مقال
Keywords: الاستراتيجية الخطابية؛ الأفعال الكلامية؛المقام؛ المقصدية؛ القصة القرآنية; discourse; strategy Intentionality;Les actes de langage;context Discursive; Quranic story.